Zhou Gong Datang untuk Melayani: Tentang Substansi Pribadi Kesadaran Beragama Konfusianisme - Shannon, Nathan (STT Reformed Injili Internasional, 2025)
This paper proposes a Reformed theological method for missiological interpretation of culture and cultural dialogue in terms of religious consciousness and uses classical Confucianism as a case study. The thesis of the paper is that, on the basis of the proposed method, a man called the Duke of Zhou was a Christlike figure for Confucius, and that therefore Confucius, for his immense influence, may or perhaps should be thought of as a herald, or rather a guardian, even an apostle untimely born, of the restorative ethic embodied in the Duke of Zhou.